2017
DOI: 10.1098/rsos.170917
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves glycolipid metabolism through regulating peroxisome proliferator activated receptor γ signalling pathway in high-fat diet-induced obese mice and 3T3-L1 adipocytes

Abstract: Curcumin is an active component derived from Curcuma longa L. which is a traditional Chinese medicine that is widely used for treating metabolic diseases through regulating different molecular pathways. Here, in this study, we aimed to comprehensively investigate the effects of curcumin on glycolipid metabolism in vivo and in vitro and then determine the underlying mechanism. Male C57BL/6 J obese mice and 3T3-L1 adipocytes were used for in vivo and in vitro study, respectively. Our results demonstrated that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
1
45
1
1
Order By: Relevance
“…Antidiabetic effect of curcumin supplement, at least in part, is due to decreasing in serum free fatty acids (Na et al, ). The possible mechanisms of the effect of curcumin on glycemia in human/animal diabetes models and in vitro may be understood as follows: (a) decrease tumor necrosis factor‐α (TNF‐α) levels (El‐Azab et al, ; El‐Moselhy et al, ), (b) decrease plasma free fatty acids (El‐Moselhy et al, ); through increasing peroxisomal fatty acid β‐oxidation) (Asai & Miyazawa, ); (c) attenuate oxidative stress (Murugan & Pari, ); (d) decrease circulating concentrations of resistin and fetuin‐A (Sahebkar, ); (e) inhibit nuclear factor‐kappa B (NF‐κB) activation (Soetikno et al, ), (f) inhibit protein carbonyl (Suryanarayana et al, ); (g) inhibits lipid peroxidation (El‐Azab, Attia, & El‐Mowafy, ), (h) inhibits lysosomal enzyme activities (Chougala et al, ); (i) induce the mRNA and protein expression of PPAR‐γ (Nishiyama et al, ; Pan et al, ); (j) active nuclear factor erythroid‐2‐related factor‐2 (Nrf2) function (He et al, ); (k) increase plasma insulin level lipoprotein lipase activity (Seo et al, ); (l) down‐regulation of JNK phosphorylation and activity (Shao‐Ling et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antidiabetic effect of curcumin supplement, at least in part, is due to decreasing in serum free fatty acids (Na et al, ). The possible mechanisms of the effect of curcumin on glycemia in human/animal diabetes models and in vitro may be understood as follows: (a) decrease tumor necrosis factor‐α (TNF‐α) levels (El‐Azab et al, ; El‐Moselhy et al, ), (b) decrease plasma free fatty acids (El‐Moselhy et al, ); through increasing peroxisomal fatty acid β‐oxidation) (Asai & Miyazawa, ); (c) attenuate oxidative stress (Murugan & Pari, ); (d) decrease circulating concentrations of resistin and fetuin‐A (Sahebkar, ); (e) inhibit nuclear factor‐kappa B (NF‐κB) activation (Soetikno et al, ), (f) inhibit protein carbonyl (Suryanarayana et al, ); (g) inhibits lipid peroxidation (El‐Azab, Attia, & El‐Mowafy, ), (h) inhibits lysosomal enzyme activities (Chougala et al, ); (i) induce the mRNA and protein expression of PPAR‐γ (Nishiyama et al, ; Pan et al, ); (j) active nuclear factor erythroid‐2‐related factor‐2 (Nrf2) function (He et al, ); (k) increase plasma insulin level lipoprotein lipase activity (Seo et al, ); (l) down‐regulation of JNK phosphorylation and activity (Shao‐Ling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the findings of a study confirmed the efficacy of curcumin supplementation in significantly reducing liver fat content, BMI, and serum levels of total cholesterol, LDL‐C, TG, glucose, and HbA1c of patients with nonalcoholic fatty liver disease and MetS (Rahmani et al, ). The multiple mechanisms of curcumin on lipids may be explained as follows: (a) decrease oxidative stress (Lin et al, ); (b) inhibit membrane translocation and GLUT2‐mediated gene expression; (c) increase expression of the advanced glycation end products receptor (Lin et al, ); (d) increase expression LDL‐receptor (enhance plasma removal and biliary excretion of cholesterol) (Sahebkar, ); (e) increase expression of genes involved in lipid accumulation (Hegarty et al, ); (f) stimulate the activity of PPAR‐γ (Hegarty et al, ); (g) activate the process of lipolysis of TGs (Pan et al, ; Vázquez‐Vela et al, ); (h) regulate adipocyte differentiation and macrophage activation (Gonzales & Orlando, ; Gustafson & Smith, ); (i) inhibit the foam cell formation (Li et al, ); (j) decrease intestinal absorption of cholesterol (Sahebkar, ); (k) downregulate several enzymes and receptors involved in lipogenesis (Sahebkar, ); (l) stimulate fatty acid oxidation, 13‐reduce glycerol lipid synthesis (Ejaz et al, ). However, it is unclear which mechanism will have the most important impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR‐γ influences the activity of several intracellular second messengers and their signaling cascade, including regulation of insulin sensitivity, glucose homeostasis, fatty acid oxidation, immune responses, redox balance, cardiovascular integrity, and cell fate . Recent studies have reported that activation of PPAR‐γ reduces the development and progression of neurodegenerative diseases by altering the expression of NF‐κB cascade . PPAR‐γ is highly expressed in hippocampal region of the brain .…”
Section: Ppar γ As a Therapeutic Target In Neurodegenerative Diseasesmentioning
confidence: 99%
“…[130][131][132] Recent studies have reported that activation of PPAR-γ reduces the development and progression of neurodegenerative diseases by altering the expression of NF-κB cascade. 131,133,134 PPAR-γ is highly expressed in hippocampal region of the brain. 135 PPAR-γ directly or indirectly influences the expression of genes (TFAM, NRF1, NRF2, Bax, and Bcl-2) that are involved in neurodegeneration.…”
Section: Ppar γ As a Therapeutic Target In Neurodegenerative Diseasmentioning
confidence: 99%